Short-term physical and psychological stress did not cause lasting changes in the integrity of the brain white matter of male rats - Barilli, Leticia Alexandrino; Pereira, Gustavo Henrique; Dias, João Pablo; Melo, Silvana Regina de (Acta Scientiarum. Health Sciences, 2024)
The effect of juvenile stress on brain morphology, and especially white matter, is poorly understood. The present study aimed to evaluate the effects of two models of stress, physical and psychological, in the juvenile phase of male rats and their long-term impact on the integrity of the brain white matter. Morphological analysis was based on two major pathways of brain connection and myelin concentration, corpus callosum (CC) and fornix. Animals were randomly assigned to three groups: Control (C), Immobilization Stress (IS), and Predator Exposure Stress (PES). The stress procedures occurred for three consecutive days from d95 of postnatal life (P25 to P27). For long-term evaluation, in adulthood (P90-P95), the brains were collected, fixed, and processed by the Klüver-Barrera technique. The collected material was evaluated using image capture and analysis in the ImageJ Software. Both models of stress studied produced no changes in body and brain weight, and all regions analyzed (genu, body, and splenium of the corpus callosum and the fornix) showed no changes in optical integrity. Thus, this study suggests that short-term juvenile stress does not cause lasting morphological effects on white matter structure, and this adaptation, in which neither reductive nor protective changes occurred, can be considered a positive adaptation.